Residue L193P Mutant of RpoS Affects Its Activity During Biofilm Formation in Salmonella Pullorum - Feng, Zheng; El Hag, Muhanad; Qin, Tao; Du, Yinping; Chen, Sujuan; Peng, Daxin (Frontiers in Veterinary Science, 2020)
The role of alternative sigma factor RpoS in regulating biofilm formation may differ in various Salmonella Pullorum strains. In this study, the biofilm-forming ability of two Salmonella Pullorum strains S6702 and S11923-3 were compared. The biofilm forming ability of S11923-3 was much stronger than that of S6702. After knocking out the rpoS gene, S11923-3rpoS had significantly reduced biofilm while S6702rpoS demonstrated similar biofilm compared with each parent strain. The analysis of RpoS sequences indicated two amino acid substitutions (L193P and R293C) between S6702 and S11923-3 RpoS. A complementation study confirmed that the expression of S11923-3 RpoS rather than S6702 RpoS could restore the biofilm-forming ability of rpoS strains and the L193P mutation contributed to the restoration of the biofilm-forming ability. Further study indicated that RpoS with the L193P mutant had significantly improved expression level and binding activity to RNAP and csgD gene promoter, which increased the efficacy of the csgD gene promoter and biofilm-forming ability. Therefore, the L193P mutation of RpoS is critical for stronger biofilm formation of Salmonella Pullorum.